Are ASD and ADHD a Continuum? A Comparison of Pathophysiological Similarities Between the Disorders. (September 2015) - Kern, Janet K.; Geier, David A.; Sykes, Lisa K.; Geier, Mark R.; Deth, Richard C.
Objective: The objective of this study was to review and compare the similarities between autism spectrum disorder (ASD) and ADHD with regard to symptomatology, neurological deficits, metabolic and endocrine-related conditions, and brain pathology.Method: A comprehensive review of the relevant research literature was carried out.Results: A number of important similarities between ASD and ADHD were identified, including recent increases in prevalence, male-biased incidence, shared involvement of sensory processing, motor and impulse control, abnormal patterns of neural connectivity, and sleep disturbances. Studies suggest involvement of androgen metabolism, impaired methylation, and heavy metal toxicity as possible contributing factors for both disorders.Conclusion: ASD and ADHD share a number of features and pathophysiological conditions, which suggests that the two disorders may be a continuum and have a common origin.